Molecular detection of Sarcocystis sp. in a kept under human care black capuchin monkey (Sapajus nigritus., Goldfuss 1809) with necrotizing encephalitis - Teng, Fwu Shing [UNESP]; Ferreira-Machado, Eduardo; Guerra, Juliana Mariotti; Ressio, Rodrigo Albergaria; dos Santos Cirqueira, Cinthya; Figueiredo, Ketlyn Bolsachini; de Carvalho, Ana Carolina Souza Ramos; de Camargo, Gabriel Corrêa [UNESP]; dos Santos, Daniel Oliveira; Rahal, Sheila Canevese [UNESP]; Rocha, Noeme Sousa [UNESP]; Oliveira, Ayisa Rodrigues; et al. (Wiley, 2024)
A senile male black capuchin monkey (Sapajus nigritus) kept under human care in a Zoo was found dead after 2 weeks presenting signals of weight loss and hyporexia. Histopathological revealed a necrotizing encephalitis. Although it was not observed microscopically, Sarcocystis sp infection was detected in brain tissue from molecular assays. These infections have been rarely described in neotropical primates, particularly associated with tissue lesions.
Keywords: Apicomplexa; pathology; primates; wildlife; zoo animals